Portuguese EQA Assessment in Parasite Morphology 26 years experience - Correia, Helena (2023)
The Parasite Morphology Programme was implemented in 1996 by the Portuguese External Quality Assessment Programme (PNAEQ), with a pilot round the previous year, which includes the assessment of stool and blood samples, as well as other matrices. The program is supported by a group of experts for sample selection and preparation, result analysis and training. Aim: Evaluation of the performance of participants in the parasite morphology program by optical microscopy (1996-2022).